Treatment options for glucocorticoid-induced osteoporosis. (12th April 2020) - Chiodini, Iacopo; Merlotti, Daniela; Falchetti, Alberto; Gennari, Luigi
ABSTRACT: Introduction: Glucocorticoid (GC) induced osteoporosis (GIOP) is the most common form of secondary osteoporosis. It develops in a dose and time dependent manner, due to a rapid and transient increase in bone resorption, followed by the inhibition of bone formation. Areas covered: In this review, the authors summarize the pathophysiology of GIOP and give discussion to the clinical management of patients taking GCs, focusing on the currently available drugs that have antiresorptive or anabolic activity on bone. Expert opinion: Despite the widespread use of GCs and their well-established detrimental skeletal effects, GIOP remains an under-diagnosed and under-treated condition. Indeed, the clinical management of GIOP is still debated, so that the recent guidelines differ in their indications for pharmacological intervention. Either bone mineral density (BMD) or algorithms such as FRAX do not completely account for the remarkable and rapid increase in fracture risk of most GC-treated patients. Moreover, while oral bisphosphonates remain the most used and cost-effective option, the potential increased benefits of more potent antiresorptive agents (e.g. denosumab and zoledronate) or anabolic compounds (e.g. teriparatide) warrant further investigation. Despite the above limitations, the assessment of fracture risk is recommended for all individuals committed to receiving oral GCs for 3 months or longer.